Analysis of Tirta Empul Development Strategy as Wellness Tourist Attraction in New Normal Era - Ni Ketut Wiwiek Agustina; Putu Gde Arie Yudhistira (Journal of Business on Hospitality and Tourism, 2021)
The Covid-19 pandemic is a very dangerous epidemic that affects the order of human lives around the world. The existence of the Covid-19 pandemic has made everyone without exception have to be able to adapt to the new life order or new normal era in accordance with health protocols. In this new normal era, many people have begun to take short, cost-effective trips and tend to seek pleasure and health simultaneously to reduce boredom and stress when forced to stay at home during lockdowns. One of the tourism trends that is coming back is Wellness Tourism. The current trend of Wellness Tourism is one of the options for restoring the passion of tourism in Bali Province which will encourage public interest in travelling. Tirta Empul is one of the tourist attractions that have the potential to support wellness tourism as a Wellness Tourist Attraction. This research was conducted in Tirta Empul which aims to analyze development strategies related to the wellness tourist attraction. This study uses data processing analysis carried out by SWOT through an analysis process of internal factors (IFAS) and external factors (EFAS). The results showed that the Grand Strategy obtained in this study is the S (Strength) - O (Opportunity) Strategy, so that there are opportunities to develop Tirta Empul as a Wellness Tourist Attraction in a New Normal Era.